Investigating the Mechanical Response of Soy-Based Polyurethane Foams with Glass Fibers under Compression at various Rates. Issue 6 (November 2015) - Obaid, N.; Kortschot, M.; Sain, M.
Polyurethane foams have very diverse mechanical properties making them suitable for a wide range of applications. Their dependence on petroleum-based constituents, however, has prompted research in the preparation and investigation of foams made from bio-based components, such as polyol derived from soybean oil. Short fiber reinforcement has been found to improve the compressive modulus and plateau stress of the foams. In this study, elastic glass fibers were used to reinforce viscoelastic polyurethane foams; the compressive behaviour of the resulting foam was observed at various strain rates. At all strain rates, the fibers reinforced the foams, improving the modulus and plateau stress when compared to the properties of neat foam. A coupling between the fiber content and strain rate-dependence was observed in the modulus and plateau stress of the foams. Lastly, despite the increase in strength and stiffness of the foams, addition of fibers did not reduce the energy absorption of the foams.